Influência da angulação do implante e tipo de intermediário na distribuição das tensões - Pellizzer, Eduardo Piza [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Sánchez, Daniela Mayumi Inatomi Kavano [UNESP]; Rinaldi, Gabriel Tozo [UNESP]; Aguirre, Carolina Calles (My University, 2010)
The aim of this study was to evaluate the influence of implant angulation and abutment type (UCLA and Estheticone) on stress distribution in screw-retained implant-supported prostheses through photoelasticity. Three models were fabricated with photoelastic resin PL-2 (Vishay, Micro-Measurements Group, Inc Raleigh, N.C., USA) containing one external hexagon implant with 3.75x10mm (Master screw, Conexão Sistemas de Prótese Ltda., Arujá, São Paulo) with 0°, 17° and 30° degrees and a screw-retained prostheses with UCLA and Estheticone abutments. The assembly was positioned in a circular polariscope; axial and oblique (45° degrees) loads of 100N were applied in fixed points on the occlusal crown surfaces by a universal testing machine. The stress generated was photographed and analyzed qualitatively with appropriate software (Adobe Photoshop®). The results demonstrated the same number of fringes for both abutment types for each angulation, with fringes increasing in the same way. A higher number of fringes were closer in the oblique loading mode. It was concluded that there was no significant difference in stress distribution in prostheses with UCLA and Estheticone abutments. Higher stress concentrations were observed with increased implant angulation. Stress concentration and intensity were higher in the oblique load than in axial load application.

O objetivo do presente trabalho foi avaliar a influência da angulação do implante e tipo de intermediário (Ucla e Esteticone) na distribuição das tensões em próteses parafusadas implantossuportadas, pelo método da fotoelasticidade. Foram confeccionados três modelos em resina fotoelástica PL-2 (Vishay, Micro-Measurements Group, Inc Raleigh, NC USA), com um implante de hexágono externo de 3,75 x 10 mm (Master screw, Conexão Sistemas de Prótese Ltda., Arujá, São Paulo) angulado a 0°, 17° e 30° com a prótese parafusada, com intermediários Ucla e Esteticone. O conjunto foi posicionado em um polariscópio circular e foi aplicada uma carga de 100 N em direção axial e oblíqua (45°), em pontos fixos na superfície oclusal das coroas, com ajuda de uma máquina ensaio universal (EMIC). As tensões geradas foram registradas fotograficamente e posteriormente analisadas qualitativamente em programa gráfico (Adobe Photoshop). Os resultados mostraram o mesmo número de franjas para os dois tipos de intermediário e as franjas aumentaram conforme o aumento da angulação. Houve um maior número de franjas, quando da aplicação de carga oblíqua. Concluiu-se que: não houve diferença significativa na distribuição das tensões nas próteses com intermediário Ucla e Esteticone. Houve maior concentração de tensões na medida em que se aumentou a angulação do implante. A carga oblíqua produziu uma maior concentração e intensidade de tensões que a carga axial.
Influence of implant angulation and abutment type on stress distribution
Keywords: Dental implants; Biomechanics; Fixed dental prostheses; Implante dentário; Biomecânica; Prótese fixa